A corpus linguistic study of the situatedness of English pop song lyrics. Issue 1 (April 2016) - Motschenbacher, Heiko
Abstract : This study uses corpus linguistic methods to investigate how the situatedness of pop song lyrics may affect their linguistic make-up. For this purpose, I compare a corpus of Eurovision lyrics (ESC-ENG) to a general pop lyrics corpus (G-Charts) which is used as a reference corpus. This is done to detect specificities of the Eurovision lyrics, which can be related to the contextual salience of Europeanness in the Eurovision Song Contest. The major focus is on semantic keyness analyses carried out with the help of Wmatrix. These analyses highlight semantic fields that occur unusually frequently or infrequently in the Eurovision lyrics in comparison to the general charts corpus. The semantic keyness analyses are further complemented by keyword analyses and a closer examination of lexical items within particular semantic fields. The results show that Eurovision lyrics construct a discursive world that differs in various respects from that of commercially successful pop songs.